EXPOSURE PACKET DATA COMMUNICATION IN COMPUTER COMMUNICATION SERVICES - Gloria Isabella Mandagie; Rafael A. Gafar., Ir. Rafael A. Gafar., Ir. (Jurnal Sistem Informasi, 1992)
Data communications in Indonesia, initially using SKDP. Until now SKDP network has reachedthe cities of Jakarta, Bandung, Surabaya, Medan, Ujung Pandang and P. Batam. Year 1992 isplanned to add another 8 Advanced Network Processor (ANP) in Denpasar, Palembang,Semarang, Balikpapan, Yogyakarta, City I (Cawang) and two cities in Kalimantan.Public switched data network is a data communication facility between the Personal Computer,Personal Computer with the Host Computer and between Host Computer with a packet switchingmanner shipments, ie per package, in which a long story broken up into packets, with a certainsize to be sent.SKDP further can be explained on the application, periperalnya, the configuration of hardware,software supports, protocols that can be served by SKDP, chargingnya and PAD System (PackedAssembly / Disassembly).By knowing the expected growth of data communications SKDP Indonesia's growing fast.